Effects of Droplet-Vitrification Cryopreservation Based on Physiological and Antioxidant Enzyme Activities of Brassidium Shooting Star Orchid - Rahmah, Safrina; Ahmad Mubbarakh, Safiah; Khor, Soo Ping; Subramaniam, Sreeramanan (Hindawi Publishing Corporation, 2015)
Protocorm-like bodies (PLBs) of Brassidium Shooting Star orchid were successfully cryopreserved using droplet-vitrification method. Vitrification based cryopreservation protocol is comprised of preculture, osmoprotection, cryoprotection, cooling, rewarming, and growth recovery and each and every step contributes to the achievement of successful cryopreservation. In order to reveal the lethal and nonlethal damage produced by cryopreservation, histological observation, scanning electron microscopy (SEM), and biochemical analysis were carried out in both cryopreserved and noncryopreserved PLBs of Brassidium Shooting Star orchid comparing with the control PLBs stock culture. Histological and scanning electron microscopy analyses displayed structural changes in cryopreserved PLBs due to the impact of cryoinjury during exposure to liquid nitrogen. Total soluble protein significantly increased throughout the dehydration process and the highest value was achieved when PLBs were stored in liquid nitrogen. Ascorbate peroxidase (APX) and catalase (CAT) showed the highest enzyme activities in both dehydration and cryostorage treatments indicating that stress level of PLBs was high during these stages.